MANAGEMENT OF ANTERIOR CROSSBITE CONCURRENTLY IMPACTED MAXILLARY LEFT SECOND PREMOLARS IN GROWING PATIENT: PENATALAKSANAAN MALOKLUSI GIGITAN SILANG ANTERIOR DENGAN IMPAKSI PREMOLAR DUA RAHANG ATAS KIRI PADA PASIEN TUMBUH KEMBANG - Ervina Sofyanti (Dentika: Dental Journal, 2011)
Anterior crossbite is a common strike anomaly that may be found in growing patient who is seeking orthodontic treatment for functional reason. On the other hand, impacted t ooth is a failure of dental eruption which is sometimes not realized by patient until having proper dental examination. The following case report described an orthodontic treatment of 10-yearold girl with straight profile and impacted maxillary left second premolars. This condition associated with arch length discrepancy causing space deficiency for second premolars eruption. The management of correcting anterior crossbite concurrently maxillary second premolars impaction started with space regaining by eliminate occlusal interference prior to distal movement of the posterior teeth. The most significant drawback of distalization is an equal and opposite mesial force tends to flare the incisors labially. After 12-months of treatment, distal movement of posterior teeth eliminating anterior crossbite and allowed spontaneous upper left second premolars eruption. At the eighteenth month of treatment, overbite and overjet value was +2mm and midline maxillary and mandible arch paralled with in relation and centric occlusion. In conclusion, early intervention for anterior crossbite and impacted second maxillary left second premolars correction in this case was based on proper treatment timing and accurate diagnose by considering patient’s growth trend.